Análisis de la disposición final de los residuos de construcción y demolición generados en el municipio de Soacha (2023)
This work is focused on analyzing the trend of final disposal of construction and demolition waste (CDW) in the municipality of Soacha, taking into account the growing interest of construction companies in generating new housing projects in this municipality that is located near the capital, the municipality of Soacha has several RCD managers, registered with the environmental authority, in this case the Regional Autonomous Corporation of Cundinamarca-CAR, however it is important to analyze the capacity that each of them has to receive all the waste generated. resulting from the acquisition of housing and the improvement of infrastructure, as well as the strategies that could be implemented in order to guide the management of this waste to its use, for this a comparison will be made of the growth rate in housing units and the trend in the final disposal in the Municipality of Soacha.